Integrated analysis of a miRNA-mRNA network related to immunity and metabolism in Macrobrachium rosenbergii infected with decapod iridescent virus 1 - Yu-Kun Jie; Jing-Wen Hao; Cui Liu; Jun-Jun Yan; Tian-Tian Ye; Ji-Lun Meng; Yu-Tong Zheng; Guo-Yuan Zou; Hong-Tuo Fu; Zhi-Min Gu (Aquaculture Reports)
Macrobrachium rosenbergii is a large, tropical freshwater crustacean species with considerable potential for commercial production. In recent years, infection with Decapod Iridescent Virus 1 (DIV1) in M. rosenbergii has been reported in aquaculture industries, causing high mortality and huge economic losses. MicroRNAs (miRNAs) are a type of RNA that regulate gene expression after transcription. However, the regulated mechanisms by which miRNAs influence the host-pathogen interactions in M. rosenbergii under DIV1 infection remain largely unexplored. In this study, hemocyte mRNA-seq and miRNA-seq analyses of M. rosenbergii under DIV1 infection were performed. Through high-throughput sequencing, we identified 2090 differentially expressed genes (DEGs) and 56 differentially expressed miRNAs (DEMs), predicting 289 differentially predicted target genes (DETGs) of the DEMs. GO and KEGG pathway enrichment analyses of the DETGs showed that multiple functional categories related to immunity and metabolism were found to be enriched, such as the PI3K-Akt signaling pathways, mTOR signaling pathway, HIF-1 signaling pathway, glycolysis signaling pathway, and tricarboxylic acid cycle. Further research suggests that PI3K-mediated immune responses may be activated by DEMs such as miR-236–5p, miR-130a-3p, and miR-365–5p, while metabolic reprogramming may be activated by DEMs such as miR-279–3p, miR-142–5p, and miR-705–5p. Moreover, we verified selected immune-related and metabolism-related mRNAs and miRNAs through qRT-PCR and confirmed the reliability of the RNA-seq results. Our study deepened the understanding of miRNA-regulated immune and metabolism responses in M. rosenbergii under DIV1 infection, laying the groundwork for further research on shrimp hemocyte antiviral responses and the development of new strategies for DIV1 prevention and treatment.